Analisis Uji Validasi Buku Panduan Video Analisis pada Materi Kinematika untuk Calon Guru Fisika - Thoha Firdaus; Ida Hamidah; Wawan Setiawan; Ida Kaniawati (JIPFRI (Jurnal Inovasi Pendidikan Fisika dan Riset Ilmiah), 2019)
A video analysis experiment guide has been made on kinematics material using the pro logger program for prospective physics teachers. This study aims to see the results of the feasibility of an experimental guide. This research method uses design and development research (DDR). The guide is validated by user experts and material experts with an average value that can be sequentially 79.69% and 87.5%. So it can be concluded that this video analysis guide is acceptable and feasible to be used by students.